Identification of the rice Rc gene as a main regulator of seed survival under dry storage conditions - Prasad C.T., Manjunath; Kodde, Jan; Angenent, Gerco C.; Hay, Fiona R.; McNally, Kenneth L.; Groot, Steven P.C. (Wiley, 2023)
Seed deterioration during storage results in poor germination, reduced vigour, and non-uniform seedling emergence. The aging rate depends on storage conditions and genetic factors. This study aims to identify these genetic factors determining the longevity of rice (Oryza sativa L.) seeds stored under experimental aging conditions mimicking long-term dry storage. Genetic variation for tolerance to aging was studied in 300 Indica rice accessions by storing dry seeds under an elevated partial pressure of oxygen (EPPO) condition. A genome-wide association analysis identified 11 unique genomic regions for all measured germination parameters after aging, differing from those previously identified in rice under humid experimental aging conditions. The significant single nucleotide polymorphism in the most prominent region was located within the Rc gene, encoding a basic helix-loop-helix transcription factor. Storage experiments using near-isogenic rice lines (SD7-1D (Rc) and SD7-1d (rc) with the same allelic variation confirmed the role of the wildtype Rc gene, providing stronger tolerance to dry EPPO aging. In the seed pericarp, a functional Rc gene results in accumulation of proanthocyanidins, an important sub-class of flavonoids having strong antioxidant activity, which may explain the variation in tolerance to dry EPPO aging.